Terrorism and mass media. (Journal of actual problems of jurisprudence, 2016)
In article is considered problem limit methods and ways, used in fight with terrorism. The Author interest the questions of the restriction freedom of speech for provision of information safety. The State must work on success its information politicians in sphere of the fight with terrorism. Law-enforcement organs must successfully co-operate with mass media.
Keywords: the terrorism; mass media; information safety